PERLINDUNGAN HUKUM BAGI PENANAMAN MODAL ASING (PMA) DI INDONESIA - Nanci Yosepin Simbolon; Muhammad Yasid; Beny Syahputra Sinaga; Nancy Saragih (Jurnal Darma Agung, 2020)
The existence of foreign investment in Indonesia is very important and strategic in supporting the implementation of national economic development and increasing economic growth in the community, which is regulated in law number 25 of 2007. This research is an empirical normative research, data collection is done by interview and literature study. Data processing is done by checking the data, the analysis in this study is done descriptive, that is, systematically doing research in the field to obtain data.The results show that in every foreign company that wants to invest in Indonesia, it must take care of the principle permit to the Investment Coordinating Board (BKPM) and the One-Stop Integrated Investment and Service Office (PTSP). So that the company can be established in Indonesia and its establishment is in accordance with the procedures of the foreign investment law so that the foreign investment company is fully under the responsibility and supervision of The Republic of Indonesia. The Government also provides relief to foreign investment in Indonesia in foreign up the cost of the entry of goods or electronic equipment for the purposes of Foreign Investment in Indonesia in investing.